Prospect and Practice of Teacher Induction in Nepal - Khadka, Kabita (Marsyangdi Journal, 2021)
The process of converting pre-service teaching into an in-service teacher is known as induction and this technique of teachers’ professional growth has been gaining momentum in the world of teacher education throughout the world. Nepal is a developing country and it has not started the teacher induction program formally yet. This study is an attempt to investigate the role and prospect of teacher induction. The study employed a descriptive method and used secondary sources to make arguments. For the argumentation, the study at first makes a claim and it is supported by already published literature. Those secondary sources of data comprise previous researchers, journals, and other standard publications. The study found that using induction, teachers around the world developed their professional abilities and their inhibitions and disappointments were removed since they got an opportunity to collaborate with professional teachers, it has become a life-long experience and different features and components of it made it more reliable and valid. The study suggests that it is extremely necessary to introduce a teacher induction program in all levels of education and if can be done teachers’ professional development can be practically achieved.